2013
DOI: 10.1002/ar.22737
|View full text |Cite
|
Sign up to set email alerts
|

SND1 Affects Proliferation of Hepatocellular Carcinoma Cell Line SMMC‐7721 by Regulating IGFBP3 Expression

Abstract: Staphylococcal nuclease domain containing 1 (SND1) is a ubiquitously expressed multifunctional protein involved in transcriptional regulation, RNA splicing and RNA metabolism. Ectopic expression of SND1 has been observed in various tumors including colon cancer, breast cancer, prostate cancer and hepatocellular carcinoma (HCC), indicating a positive role of SND1 in tumor initiation and progression. However, the exact role of SND1 in cancers has not been thoroughly investigated. In the present study, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…In hepatocellular carcinoma, it has been found that 1) SND1 could affect SMMC-7721 cells proliferation by regulating IGFBP3 expression and IGF signaling pathway [20]; 2) SND1 promotes tumor angiogenesis in human hepatocellular carcinoma through pathways that involves nuclear factor κB and miR-221 [21]; and 3) SND1 overexpression deregulates cholesterol homeostasis [22]. Of the few studies that have investigated the role of SND1 in CRC, one paper found that SND1 may contribute to the posttranscriptional regulation of key players in colon cancer development, including APC and β-catenin [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In hepatocellular carcinoma, it has been found that 1) SND1 could affect SMMC-7721 cells proliferation by regulating IGFBP3 expression and IGF signaling pathway [20]; 2) SND1 promotes tumor angiogenesis in human hepatocellular carcinoma through pathways that involves nuclear factor κB and miR-221 [21]; and 3) SND1 overexpression deregulates cholesterol homeostasis [22]. Of the few studies that have investigated the role of SND1 in CRC, one paper found that SND1 may contribute to the posttranscriptional regulation of key players in colon cancer development, including APC and β-catenin [18].…”
Section: Discussionmentioning
confidence: 99%
“…Though SND1 could promote tumor progression through regulating calcium binding proteins, signaling pathways, non-coding RNAs or hormones in different types of other cancer [19][20][21][22], little is known about the exact mechanism of SND1 in CRC. In the present study, we first conducted the SND1 mRNA and protein expression levels https://doi.org/10.1515/biol-2017-0028…”
Section: Introductionmentioning
confidence: 99%
“…72 Furthermore, TSN could affect hepatocellular carcinoma (HCC) progression by two distinct pathways. 70,73 First, as a member of RISC complex, TSN interacts with AEG-1 leading to the increased degradation of tumor suppressor mRNAs. 70 On the other hand, a negative regulator of insulin-like growth factor (IGF) pathway, an insulinlike growth factor-binding protein 3 (IGFBP3), was reported to be significantly overexpressed in TSN knockdown HCC cells, suggesting the contribution of TSN to cell proliferation, colony and tumor formation.…”
Section: Role Of Tsn In Carcinogenesis and Cell Deathmentioning
confidence: 99%
“…70 On the other hand, a negative regulator of insulin-like growth factor (IGF) pathway, an insulinlike growth factor-binding protein 3 (IGFBP3), was reported to be significantly overexpressed in TSN knockdown HCC cells, suggesting the contribution of TSN to cell proliferation, colony and tumor formation. 73 Another important process regulated by TSN is angiogenesis ( Figure 5). TSN promotes angiogenesis in HCC by activating the NF-kB, resulting in the induction of the Figure 4 Role of TSN in the cross-talk between different pathways post-transcriptionally regulating gene expression.…”
Section: Role Of Tsn In Carcinogenesis and Cell Deathmentioning
confidence: 99%
“…SND1 is overexpressed in HCC (85); knockdown of SND1 leads to reduced HCC cell proliferation, clone formation and tumor formation in nude mice (86); and it also regulates HCC angiogenesis by activation of NF-κB and miR-221 inducing angiogenic factors such as angiogenin and CXCL16 (87). The identification of SND1 as an AEG-1-interacting protein was found using two independent approaches, including yeast two hybrid screening using a human liver cDNA library and isolation of AEG-1 interacting proteins by co-immunoprecipitation followed by mass spectrometry.…”
Section: Aeg-1-interacting Protein Snd1mentioning
confidence: 99%